Ingsun Titip Tajug Lan Fakir Miskin, Sunan Gunung Jati's Advice Toward True Human Plenitude - Qomaruddin, Muhammad (Jurnal Studi Sosial Keagamaan Syekh Nurjati, 2024)
Sunan Gunung Jati is one of God's guardians who struggled to spread Islam in the archipelago and has a famous advice “Ingsun Titip Tajug lan Fakir Miskin”. This research aims to explore the values of Sunan Gunung Jati's famous advice comprehensively from a theological perspective. The method used is a qualitative method with a descriptive approach through literature review. The results showed that Sunan Gunung Jati's advice was not only to take care of the tajug (musala) and the poor. However, the value of Ilahiyyah and Insaniyyah reveals the depth of the message to the concept of being a complete human being. The foundation of the naqli argument also illustrates how important it is to maintain the relationship between a servant and his God and fellow creatures. Through theological analysis, the message of Ingsun Titip Tajug Lan Fakir Miskin can be interpreted as profound advice so that humans, especially Muslims, can become pious and humane individuals. Not apart from that, the Prophet Muhammad is also a true human figure who provides an exemplary attitude so that his people strive towards a complete human being by maintaining a balance of hablumminallah and hablumminannass. This research recommends that religious leaders be able to maintain and implement Sunan Gunung Jati's famous advice.